IMPLEMENTASI LAGU “SENTUHAH BOLEH” SEBAGAI MEDIA EDUKASI DALAM PENCEGAHAN PELECEHAN SEKSUAL PADA ANAK DI TK BUDI MULIA KECAMATAN DAHA UTARA KANDANGAN - Asiah; Salhah; Yuliani (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2024)
Early age is a potential period for learning for children. Various knowledge can be taught from an early age, one of which is about sex education and prevention efforts. It is very important to convey an understanding of sexual prevention to children, so that children can know what body parts other people can and cannot touch. The singing method is one method that children really like and enjoy. The song "Touch is Allowed" is an educational medium used by teachers at Budi Mulia Kindergarten as a form of providing understanding about sex education and sexual prevention for children in Kindergarten. The research method used is qualitative research, with the research subjects being the school principal, teachers and children at Budi Mulia Kindergarten. The data collection methods used were observation and interviews. This research aims to describe the implementation of the song "Touch is Allowed" as an educational medium in preventing sexual abuse of children at Budi Mulia Kindergarten, Daha Utara Kandangan District. The results of the research show that the implementation of the song "touch is allowed" as an educational medium for sexual prevention in children is effective. This can be seen when children are able to remind friends who do bad things and immediately reprimand them by singing the song "touch is allowed" and children feel happy singing the song "touch is allowed" as an educational medium for sexual prevention in kindergarten